2022
DOI: 10.1097/j.pain.0000000000002760
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvanted recombinant zoster vaccine decreases herpes zoster-associated pain and the use of pain medication across 3 randomized, placebo-controlled trials

Abstract: Herpes zoster (HZ) and HZ-associated pain greatly affect patients' quality of life, particularly in older and immunocompromised adults, for whom comorbidities and polypharmacy are often reported. Three phase III, randomized, placebo-controlled clinical trials have reported the adjuvanted recombinant zoster vaccine (RZV) as highly efficacious in preventing HZ and reducing pain severity in healthy adults $50 years old (Zoster Efficacy Study [ZOE]-50 study, NCT01165177) and $70 years old (ZOE-70; NCT01165229) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…However, estimating the QALYs lost for HZ and PHN is challenging, as evidenced by the rather different values used in the analysis by McGirr et al [ 14 ] and the current study, which used newer values [ 41 ]. Moreover, the QALYs lost per case of HZ and PHN were assumed to be the same among vaccinated and unvaccinated individuals, but breakthrough HZ tends to be shorter [ 59 ]. Thus, the ICERs may have been overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…However, estimating the QALYs lost for HZ and PHN is challenging, as evidenced by the rather different values used in the analysis by McGirr et al [ 14 ] and the current study, which used newer values [ 41 ]. Moreover, the QALYs lost per case of HZ and PHN were assumed to be the same among vaccinated and unvaccinated individuals, but breakthrough HZ tends to be shorter [ 59 ]. Thus, the ICERs may have been overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Data from the ZOE-70 study indicated that RZV significantly reduced HZ-associated pain medication use and duration of pain medication use in participants with confirmed HZ 73 . Figure 2 presents the distribution of the individual maximal ZBPI “worst-pain” scores experienced over the entire HZ episode for the ZOE-50 study 33 .…”
Section: Recombinant Zoster Vaccinementioning
confidence: 99%
“…This sustained immune response is anticipated to remain as strong as the initial immune response above baseline for up to 15 years post-vaccination [142,144]. Moreover, RZV reduces the duration of HZ-associated pain and enhances patient quality of life by reducing the need for analgesics, even in breakthrough cases [145]. Thus, RZV vaccination not only reduces the incidence of HZ but also its complications and the utilization of medical resources, potentially leading to a considerable reduction in the public health burden [146].…”
Section: Recombinant Zoster Vaccinementioning
confidence: 99%